Alternative futures in political discourse. (May 2021) - Cap, Piotr
This paper describes ways in which political speakers define and legitimize future policies by construing different policy options in terms of 'privileged' and 'oppositional' futures. Privileged and oppositional futures are conceptual projections of alternative policy visions occurring in quasi-dialogic chunks of speech, revealing specific evidential, mood, and modality patterns. Privileged future involves speaker's preferred vision and is articulated through absolute modality and evidential markers which derive from factual evidence, history, and reason. Oppositional future involves antagonistic and plainly threatening vision, expressed by probabilistic modality and interrogative mood. For psychological reasons, oppositional future is normally communicated first, allowing a swift response from the privileged future expressed in the speaker-preferred vision. The paper demonstrates that privileged and oppositional futures blur traditional distinctions between dialog and monolog and thus invite heterogeneous methods and instruments of analysis. It discusses the most productive interdisciplinary tools (critical, SFL and rhetorical tools, socio-psychological models), and their implementation in analysis of lexical manifestations of alternative futures in political discourse, such as immigration and anti-terrorist discourse.